PEMANFAATAN CASHEW NUT SHELL LIQUID SEBAGAI SUMBER FENOL ALAMI PADA INDUSTRI - Juniaty Towaha; Nur Rofiq Ahmadi (Jurnal Tanaman Industri dan Penyegar, 2011)
Use of cashew nut shell liquid as sources of phenol in industries. Cashew Nut Shell Liquid (CNSL) is a dark brown viscous liquidextracted from cashew nut shell. The main components of CNSL that is anacardic acid, cardanol and kardol which is a natural phenol compounds.Cardanol compounds have chemical structures similar to phenols synthetic, so the opportunity to substitute or replace the synthetic phenoliccompounds from petroleum derivatives, whose the sources are running low. CNSL compound and its components anacardic acid, cardanol and kardol,and derivatives products have benefits that vary in different industries, as well as substitution of synthetic phenol as a so urce of phenolic compounds,such as the pharmaceutical industry, insecticides, adhesives, varnishes and paints, brake and clutch linings, laminating resin, epoxy resin, castingmetal, cement, surfaktants, rubber formulations and various chemical industries. Until now, Indonesia's cashew nut shell not fully utilized, most stillis a waste, so the production of CNSL in Indonesia is still very low. The potential for production of CNSL in Indonesia is actually quite large,therefore, given the various benefits of CNSL and its derivatives in various industries, as well as its superiority in the composition of the molecularstructure and advantages as an environmentally friendly renewable material, then it's time CNSL potential contained in the ca shew nut shell can toproductivity and well developed.